Hubungan Hukum dan Masyarakat - Muhammad Aini (PT. Hasba Edukasi Mandiri, 2025)
Law and society have a dynamic relationship that influences each other. This research aims to analyze the interaction between law and social norms, as well as the challenges faced in the context of a pluralistic Indonesian society. The method used is a literature review with a legal sociology approach. The findings show that laws are often not in line with local cultural values, resulting in societal non-compliance with positive legal norms. In addition, technological developments and globalization exacerbate these inconsistencies, creating a need for more responsive and inclusive regulation. The implications of this study show the importance of community participation in the law-making process and the need for regulatory reforms that are adaptive to social and technological developments. Thus, the law is expected to function as an effective instrument of justice and social order.